2020
DOI: 10.1371/journal.pone.0228910
|View full text |Cite
|
Sign up to set email alerts
|

An improved strategy for CRISPR/Cas9 gene knockout and subsequent wildtype and mutant gene rescue

Abstract: A fluorescence marker mOrange was inserted to the popular pLentiCrispr-V2 to create pLentiCrispr-V2-mOrange (V2mO) that contained both a puromycin selection and a fluorescent marker, making viral production and target transduction visible. Lentiviruses packaged with this plasmid and appropriate guide RNAs (gRNAs) successfully knocked out the genes RhoA, Gli1, and Gal3 in human gastric cancer cell lines. Cas9-gRNA editing efficiency could be estimated directly from Sanger electropherograms of short polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…The cloned library was then packaged into lentivirus and used to transfect HeLa GFP-LC3 cells. Sorting of the transfected and untransfected cells by FACS showed that ∼15% of the transfected cells lost GFP expression (Figure 4B , Supplemental Figure S3), comparable to previous studies looking at CRISPR efficiency ( 28 ). Sequencing of the incorporated spacers and GFP mutations in each pool showed that all eight potential spacers could be found in the GFP-negative pool and mutations occurred at all four sites (Figure 4C ).…”
Section: Resultssupporting
confidence: 87%
“…The cloned library was then packaged into lentivirus and used to transfect HeLa GFP-LC3 cells. Sorting of the transfected and untransfected cells by FACS showed that ∼15% of the transfected cells lost GFP expression (Figure 4B , Supplemental Figure S3), comparable to previous studies looking at CRISPR efficiency ( 28 ). Sequencing of the incorporated spacers and GFP mutations in each pool showed that all eight potential spacers could be found in the GFP-negative pool and mutations occurred at all four sites (Figure 4C ).…”
Section: Resultssupporting
confidence: 87%
“…The cloned library was then packaged into lentivirus and used to transfect HeLa GFP-LC3 cells. Sorting of the transfected and untransfected cells by FACS showed that approximately 15% of the transfected cells lost GFP expression ( Figure 3B, Supplemental Figure 2), comparable to previous studies looking at CRISPR efficiency 22 .…”
Section: Gfp Library and Fluorescent Knockout Screensupporting
confidence: 87%
“…To overcome both hurdles, we used modified cDNAs for gene rescue. In case of CR1SPR/Cas9 gene knockout, because Cas9 cleaves where gRNA binds, one or a few nucleotides in the gRNAS binding site of the CD44v6 and YB-1 were modified by three nucleotides, while the amino acid sequences remained unchanged as described previously in generating shRNA resistant constructs and gRNA rescue constructs [ 57 , 58 , 173 ]. Total cell lysates were examined by Western blot analysis for the indicated proteins and β-tubulin or β-actin were used as internal standards.…”
Section: Methodsmentioning
confidence: 99%